ACCOUNTING STUDENTS’ PERCEPTIONS ON THE EXPRESSION OF PROFESSIONAL JUDGMENT AND ETHICS IN THE ACCOUNTING FIELD - CERNUȘCĂ, Lucian; BALACIU, Diana Elisabeta (Annales Universitatis Apulensis Series Oeconomica, 2014)
This study aims to present the accounting students’ perception regarding the manifestation of accounting judgment and ethics in accounting in the current harmonization of the Romanian accounting system to IFRS and European regulations The main objective of our research is to study the perception of professional accountants on the expression of professional judgment and ethics in the accounting field, the research method used was survey (poll), the research instrument is the questionnaire. Most of those interviewed would not welcome the request of the entity management to seek professional judgment to achieve a desired result in accounting and the ethical behavior of the manager and of the professional accountant represent a crucial element in terms of getting an accurate picture of the financial position and the performance of the entity. The accounting students surveyed believe that modern IT technology working in the accounting area cannot replace professional judgment.